Dampak Sentralisasi Perizinan Pertambangan terhadap Perlindungan Lingkungan Hidup - Maulana, Syukron; Firmansyah, Firmansyah; Noveriansyah, Eri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines the impact of mining permit centralization on environmental protection in Indonesia, particularly following Law No. 3 of 2020. The research addresses the critical tension between centralizing administrative authority for mining permits with the central government while maintaining effective environmental governance and regional autonomy. Using normative legal analysis and literature review, this study identifies that centralization of mining permits, while intended to streamline bureaucracy and improve investor certainty, has paradoxically weakened environmental protection mechanisms by diminishing local government capacity for environmental monitoring and enforcement, reducing community participation in environmental decision-making, and creating coordination gaps between central and local authorities. The findings reveal that centralized licensing has contributed to weak oversight of mining environmental compliance, increased environmental degradation in mining areas, and limited accountability for environmental damages. Recommendations include establishing collaborative governance models that balance centralization with localized environmental management, strengthening inter-governmental coordination mechanisms, mandating meaningful community participation in environmental assessment processes, and reinforcing independent environmental monitoring systems separate from permit issuance authorities.